An observational study of clinico-pathological characteristics of gynecological tumors and mode of treatment - Ashwini R,; Ravi N Patil,; Shiny Varghese,; Nalini Arun Kumar,; Sathyavani C, (Asian Journal of Medical Sciences, 2024)
Background: Gynecological malignancies are a group of various malignancies of the female reproductive system which included cancers of the ovary, cervix, uterus, vulva, vagina, and also gestational trophoblastic neoplasia. Aims and Objectives: The aim of this study was to study the clinical profile, different histopathological types of gynecological tumors, and mode of treatment. Materials and Methods: Study was conducted on 94 patients from June 2022 to December 2022. Results: Mean age of study population was 49.54±14.54 years. On radiological examination, out of total 52 ovarian cancers, cysts were present in 14 (14.89%) women, solid cysts in 16 (17.02%), papillary projections in 9 (9.57%), vascularity in 11 (11.70%), and lymphadenopathy in 2 (2.12%) women. The Pipelle biopsy results showed complex hyperplasia with atypia in 6 women (6.38%), endometrial carcinoma in 2 women (2.12%), focal atypia in 3 women (3.19%), and simple hyperplasia with atypia in 7 women (7.44%). On Pap smear/liquid based cytology, 1 (1.06%) woman each had atypical squamous cells, HSIL cannot be excluded, atypical squamous cells of undetermined significance, high-grade squamous intraepithelial lesion, and low-grade squamous intraepithelial lesion. No intraepithelial lesion or malignancy was found in 82 (87.23%) women. Present study showed that cervix cases was 10 (10.63%), endometrium 30 (31.91%), and vaginal 1 (1.06%). Majority of women in the present study, that is, 53 (56.38%) had ovarian tumors. In endometrial cancer, endometrioid adenocarcinoma, that is, 15 (50%) followed by simple endometrial hyperplasia without atypia and complex endometrial hyperplasia with atypia, that is, 4 (13.33%) each. Conclusion: Maximum number of patients having various gynecological tumors presented with stage II disease and above but maximum women with ovarian cancer reported with stage III and stage IV. These results clearly explained that ovarian cancer usually had non-specific or misleading symptoms as compared to cervical cancer which reported few specific symptoms.